CONFESSING HISTORY: A RESPONSE. - Kennedy, Rick (Fides et historia, 2011)
The article discusses the anthology "Confessing History" as related to the history of the organization the Conference on Faith and History (CFH) and the history of Christian historians within the profession at large. It responds to the articles "Confessing History: Retrospect" by Jay Green and "Confessing History: Prospect" by Eric Miller. Particular focus is given to the CFH's role in postmodern critiques of modernism. According to the author, the Christian themes of faith and vocation can help postmodernist historians recover the same kinds of social knowledge which existed in pre-modern humanism. Details related to the role of evangelicalism in the CFH are presented. Other topics include objectivity, liberalism, and Aristotelian thought.